2022
DOI: 10.3390/cancers14235817
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis Reveals the Temporal Acquisition of Pathway Alterations during the Evolution of Cancer

Abstract: Cancer metastasis is the lethal developmental step in cancer, responsible for the majority of cancer deaths. To metastasise, cancer cells must acquire the ability to disseminate systemically and to escape an activated immune response. Here, we endeavoured to investigate if metastatic dissemination reflects acquisition of genomic traits that are selected for. We acquired mutation and copy number data from 8332 tumours representing 19 cancer types acquired from The Cancer Genome Atlas and the Hartwig Medical Fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…This indicates that on a genomic level, there is no difference between the molecular drivers of cancer between small and large tumors. These results thus follow the pattern of previous research, where we and others have found that there is no signi cant difference between the cancer driver landscape between primary and metastatic tumors 27,48 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This indicates that on a genomic level, there is no difference between the molecular drivers of cancer between small and large tumors. These results thus follow the pattern of previous research, where we and others have found that there is no signi cant difference between the cancer driver landscape between primary and metastatic tumors 27,48 .…”
Section: Discussionsupporting
confidence: 91%
“…For the enrichment analysis we looked at cancer driver mutations. Mutations were annotated as driver events using Annovar 26 as previously described in Ahrenfeldt et al 27 . Brie y we used PolyPhen 28 and SIFT 29 to predict if mutations were deleterious (tumor suppressor genes) or pathogenic (oncogenes).…”
Section: Enrichment Analysismentioning
confidence: 99%
“…While this gene set is of limited scope relative to the full size of the human genome, these genes harbored more than 50% of the cancer driver mutations found in 2520 metastatic tumors analyzed by the HMF study [ 8 ], making it valid for the analysis of cancer driver mutations across the largest cohort of samples analyzed to date. Consistent with previous work suggesting clonal bottlenecking is common during metastatic dissemination [ 9 11 , 14 ], we observed an increase in tumor mutation burden and chromosomal instability in metastatic tumors ( Figure 1A ). However, individual driver mutations showed limited variation between primary and metastatic disease.…”
supporting
confidence: 92%
“…When we consider our own recent work [ 12 , 14 ] and that of others [ 1 , 8 11 ], there is limited evidence for the existence of specific gatekeeper mutations. Rather, the strong correlation observed between genomic events in primary and metastatic tumors indicate that in the absence of treatment, the evolutionary pressures are similar and from a genomic standpoint mostly focused on acquisition of aggressive cancer traits through inactivation of tumor suppressor genes such as TP53, and activation of proliferative genes such as MYC.…”
mentioning
confidence: 99%